HER-2, EGFR, Cox-2 and Ki67 expression in lymph node metastasis of canine mammary carcinomas: Association with clinical-pathological parameters and overall survival. (June 2016) - Araújo, M.R.; Campos, L.C.; Damasceno, K.A.; Gamba, C.O.; Ferreira, E.; Cassali, G.D.
Abstract: Studies about canine mammary tumors based on single molecular markers probably cannot accurately account for the heterogeneity of this disease, and the investigation of multiple molecular alterations in primary tumors and their metastases, in conjunction, has assumed great importance for the understanding of mammary tumor progression. In the present study, we selected 54 primary mammary carcinomas with lymph node metastasis (T1, 2, 3N1M0), 29 primary mammary carcinomas without metastasis (T1, 2, 3N0M0), and 25 canine lymph nodes metastasis to evaluate the immunohistochemical expression of HER-2, EGFR, Cox-2 and Ki67 and its association with clinical-pathological parameters and overall survival. Our results found a concordance between the expression of HER-2 (K coefficient: 0.250), Cox-2 (K coefficient: 0.571), and Ki67 (K coefficient: 0.397) and a discordance between EGFR expression (K coefficient: − 0.195) in primary mammary carcinomas and paired lymph node metastasis. Furthermore, a high Ki67 index (> 24%), large tumor size and the presence of angiolymphatic invasion in canine primary mammary carcinoma with lymph node metastasis plus the presence of extracapsular extension in lymph nodes metastasis were also related to worse prognoses and shorter overall survival ( P < 0.05). In conclusion, our study demonstrates that primary mammary carcinomas with high expression of HER-2, Cox-2 and Ki67 also show high expression of these markers in paired lymph node metastasis. Moreover, the expression of these molecular markers in lymph nodes metastasis did not demonstrate a prognostic relevance. Highlights: A high expression of HER-2, Cox-2 and Ki67 in primary mammary carcinomas and in paired lymph node metastasis was observed. A high Ki67 index in canine mammary carcinomas with lymph node metastasis was related to poor prognosis. The presence of angiolymphatic invasion in mammary carcinomas with lymph node metastasis was related to shorter survival. The presence of extracapsular extension in lymph nodes metastasis was related to shorter survival.